Reconstruction of Islamic Boarding Schools: Curriculum, Management and Educational Ethics Perspective of KH. Imam Zarkasyi - Elyunusi, Melikaijihan; Abd Haris; Marno (EDUTEC : Journal of Education And Technology, 2024)
As a form of Islamic education in Indonesia, the existence of Islamic boarding schools as Islamic educational institutions with advantages both in terms of scientific tradition and in terms of transmission and intensity of Muslims is threatened by the current of globalization. Reform and reconstruction of Islamic education and its institutions seem to need to be carried out immediately, especially considering developments in the global world that require every Islamic educational institution to continue to improve itself in order to continue to exist. This article attempts to reconstruct the thoughts of one Islamic education figure (KH. Imam Zarkasyi) regarding the renewal of Islamic boarding schools as traditional Islamic educational institutions. The extent to which the concepts of this figure can be used as a model for modernizing traditional Islamic educational philosophy to suit the demands of Muslim society's modernization process would require further research. This study only discusses his concepts for reforming curricula, strengthening institutional administration, and promoting Islamic boarding school principles. KH. Imam Zarkasyi developed a number of his main concepts in light of the literature review. First of all, he asserted that the Islamic education curriculum emphasized modern science in addition to religious knowledge, necessitating that student be proficient in both Arabic and English. Secondly, in order to fortify Islamic boarding schools, it is imperative to enhance the institutional management of these establishments and oversee waqf in a reliable and contemporary manner. In the third section, he highlighted the importance of sincerity, simplicity, independence, ukhuwah, and freedom in the development of Islamic boarding school ideals. The Gontor Islamic Boarding School's outward character must be based on these five values.